Pengaruh Pengungkapan Corporate Social Responsibility Pada Nilai Perusahaan Dengan Kinerja Lingkungan Sebagai Pemoderasi - Purawan, Ngakan Made Dwi; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 30 No 2 (2020), 2020)
This study aims to determine the effect of Corporate Social Responsibility disclosure on company value and determine environmental performance moderating the effect of Corporate Social Responsibility disclosure on company value on the Indonesia Stock Exchange. This research was conducted on oil palm plantation sector companies listed on the Indonesia Stock Exchange in the 2014-2018 period. The sample in this study used a purposive sampling technique. The analysis technique used is the Moderated Regression Analysis (MRA) technique. The results showed that Corporate Social Responsibility did not affect the value of the company. This shows that even though the company has revealed CSR, it does not guarantee an increase in the value of the company. Environmental performance is not able to strengthen the effect of Corporate Social Responsibility disclosure on firm value. This shows that the items of environmental performance do not match the CSR disclosures made by the company. Keywords: CSR; Company Value; Environmental Performance.